The Influence of Investment Decisions and Corporate Financial Performance on Tax Avoidance: A Cross-country Study - Salsabila Salsabila; Yossi Diantimala (Jurnal Dinamika Akuntansi dan Bisnis, 2023)
This study investigates the influence of investment decisions and corporate financial performance on tax avoidance. We employed mining companies listed on the Asia Pacific Stock Exchanges from 2017 to 2021. The purposive sampling technique was applied to select 40 out of 97 top Australian, Indian, and Indonesian mining companies (200 firm-year observations). To test the hypotheses, the data was then analyzed comparatively using multiple linear regression analysis. The results show that investment decisions and corporate financial performance simultaneously affect tax avoidance. Partially, investment decisions has a significantly positive effect on tax avoidance, and corporate financial performance also has a significantly positive effect on tax avoidance. The results suggest that investment decisions and firm performance motivate managers to tax avoidance.